Biosafety Initiatives in BMENA Region: Identification of Gaps and Advances - Khan, Erum; Ahmed, Nayla; Temsamani, Khalid R.; El-Gendy, Atef; Cohen, Murray; Hasan, Ariba; Gastfriend, Hilliard; Cole, Jennifer (Frontiers in Public Health, 2016)
Introduction The objectives of this study were to identify and assess the impact of capacity-building biosafety initiatives and programs that have taken place in the broader Middle East and North Africa (BMENA) region between 2001 and 2013, to highlight gaps that require further development, and to suggest sustainable ways to build cooperative regional biosafety opportunities. Methods A cross-sectional study was conducted with two aspects (1) thorough desktop review of literature for all biosafety/biosecurity-related activities in the study countries, such as seminars, conferences, workshops, policy documents, technology transfer, sustained scientific endeavors between countries, etc. and (2) an online survey of scientists in countries in the region to get first-hand information about biosafety and biosecurity initiatives and gaps in their country. Results A total of 1832 initiatives of biosafety/biosecurity were recorded from 97 web links; 70.68% (n = 1295) initiatives were focused on raising general awareness among the scientific community about biosafety/biosecurity/biocontainment. The most frequent areas of interest were biorisk management in biomedical and biotechnology laboratories 13% (n = 239), followed by living modified organisms (LMOs) 9.17% (n = 168). Hands-on training accounted for 2.67% (n = 49) of initiatives. Online survey results confirmed desktop review findings; however, the response rate was 11%.